Breaking the cycle: Iraq following the military defeat of Islamic State - Maria-Louise Clausen (Danish Institute for International Studies (DIIS), 2019)
Islamic State in Iraq no longer controls territory, but although security is better in Iraq than in recent years, with parliamentary elections being held in May 2018, Iraq faces substantial challenges. This report focuses on three areas of special importance, namely the fragmentation of security provision, the lack of legitimate political institutions, and the effects of corruption and nepotism on the economy.
Keywords: 300